2020
DOI: 10.3390/rs12244008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Modelling Mangrove Phenology from Satellite Images: A Case Study from Northern Australia

Abstract: Around the world, the effects of changing plant phenology are evident in many ways: from earlier and longer growing seasons to altering the relationships between plants and their natural pollinators. Plant phenology is often monitored using satellite images and parametric methods. Parametric methods assume that ecosystems have unimodal phenologies and that the phenology model is invariant through space and time. In evergreen ecosystems such as mangrove forests, these assumptions may not hold true. Here we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Factors such as tidal regime 9 and wave energy 37 are also likely to be relevant: the far north of Australia experiences a diurnal mesotidal regime with low wave energy which plays an important role in sediment dynamics and mangrove distribution. Additionally, phenological differences by site and species 35 , 38 that mediate the impact of climate extremes and non-climatic factors (e.g., geomorphological factors such as soil depth) may also be relevant. Our use of an average mangrove forest recovery time of 10 years may not represent all mangrove forests, as recovery time will be dependent on localised environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as tidal regime 9 and wave energy 37 are also likely to be relevant: the far north of Australia experiences a diurnal mesotidal regime with low wave energy which plays an important role in sediment dynamics and mangrove distribution. Additionally, phenological differences by site and species 35 , 38 that mediate the impact of climate extremes and non-climatic factors (e.g., geomorphological factors such as soil depth) may also be relevant. Our use of an average mangrove forest recovery time of 10 years may not represent all mangrove forests, as recovery time will be dependent on localised environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be exacerbated with higher average air temperatures in subtropical regions where the evergreen canopy is active most of the year (Whelan et al, 2013), which causes uncertainty in the signal of phenophase transition. Furthermore, warmer winters and higher water availability in summer had a significant impact on estimating VCP metrics for Re, as variation in Re leads to prolonged growing season and multi‐peak behavior in summer (Younes et al, 2020). In addition, we found that the date of fall senescence derived from the 2‐band EVI was often mismatched with modeled Re ( p < 0.01) (Appendix S1: Figure S4), in agreement with Wu et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…These day‐to‐day carbon exchange anomalies will be reflected in phenological modeling, that is, causing multiple peaks in the phenophases during the growing season (Appendix S1: Figures S1–S2). This will make the traditional functions assuming single‐peak seasonal dynamics unable to adequately characterize phenological patterns, that is, overestimating or underestimating the length of the active season (Younes et al, 2020; Zhou, 2018). While the functional form and phenological metric extraction algorithms tested in this study assume unimodal behavior, extraction methods based on curvature, fixed thresholds, or dynamic thresholds may be more suitable for stable ecosystems (Younes et al, 2020; Zhou, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Younes [2] explored and developed a novel, data-driven approach to extract plant phenology of six different mangrove forests across Australia. They used Landsat imagery and Generalized Additive Models (GAMs) to derive phenology.…”
Section: Figurementioning
confidence: 99%